Biochemical and genetic evidence for a pseudoknot structure at the 3' terminus of the poliovirus RNA genome and its role in viral RNA amplification. - Jacobson, S J (1993)
The sequences in the plus-stranded poliovirus RNA genome that dictate the specific amplification of viral RNA in infected cells remain unknown. We have analyzed the structure of the 3' noncoding region of the viral genome by thermodynamic-based structure calculation and by chemical and enzymatic probing of in vitro-synthesized RNAs and provide evidence for the existence of an RNA pseudoknot structure in this region. To explore the functional significance of this structure, revertants of a mutant bearing a lesion in the proposed pseudoknot and exhibiting a temperature-sensitive defect in viral RNA synthesis were isolated and mapped. The results of this genetic analysis established a correlation between the structure of the 3' terminus of the viral RNA and its function in vivo in RNA amplification. Furthermore, phylogenetic analysis indicated that a similar structure could be formed in coxsackievirus B1, a related enterovirus, which further supports a role for the pseudoknot structure in viral RNA amplification in infected cells.